A framework to assess compliance training effectiveness: The case of banks in South Africa - Marié D. Botha; Stephanus P. Van der Merwe (SA Journal of Human Resource Management)
Orientation: Compliance functions constitute a major cost factor for banks, with challenges in demonstrating training effectiveness.